Mapping civic engagement: A case study of service-learning in Appalachia. (March 2016) - Mann, Jessica; Casebeer, Daniel
This study uses social cartography to map student perceptions of a co-curricular service-learning project in an impoverished rural community. As a complement to narrative discourse, mapping provides an opportunity to visualize not only the spatial nature of the educational experience but also, in this case, the benefits of civic engagement. The authors suggest that short-term immersion programs can provide students, regardless of their previous experiences with service, with opportunities to develop dispositions for active citizenship. Their maps, which envision a heterotopic space in two dimensions, examine the relationship between thought and action, specifically between empathy and apathy, and illustrate how what the students brought to the experience, in terms of their motivations and inclinations toward service-learning, as well as what they took away, in terms of their likelihood to participate in future service, ultimately led to individual growth and transformation.